[POSTER] Geometric Mapping for Color Compensation Using Scene Adaptive Patches - Jong Hun Lee; Yong Hwi Kim; Yong Yi Lee; Lee, Kwan H. (2015 IEEE International Symposium on Mixed and Augmented Reality, 2015)
The SAR technique using a projector-camera system allows us to make various effect on a real scene without physical reconstitution. In order to project contents on a textured scene without color imperfections, geometric and radiometric compensation of a projection image should be conducted as preprocessing. In this paper, we present a new geometric mapping method for color compensation in the projector-camera system. We capture the scene and segment it into adaptive patch according to the scene structure using the SLIC segmentation. The piece-wise polynomial function is evaluated for each patch to find pixel-to-pixel correspondences between the measured and projection images. Finally, color compensation is performed by using a color mixing matrix. Experimental results show that our geometric mapping method establishes accurate correspondences and color compensation alleviates the color imperfections which is caused by texture of a general scene.